Resíduos de tetraciclinas, aminoglicosídeos e fluoroquinolanas em leite por CLAE-EM/EM - Maria de Fátima Gomides (2015)
Tetracyclines, aminoglycosides and fluoroquinolones residues in milk by HPLC-MS/MS. A high performance liquid chromatography method coupled with a triple quadrupole mass spectrometer/ion trap (HPLC-MS/MS) was developed and validated to analyze antibiotic residues in milk, among them, aminoglycosides (gentamicin and neomycin) fluoroquinolones (ciprofloxacin, norfloxacin and enrofloxacin) and tetracyclines (tetracycline, oxitetraciclinas, clortetraciclinas and doxycycline). Extraction of the antibiotic residues was carried out with 5% trichloroacetic acid (TCA) followed by centrifugation. Sulfaphenazole was used as internal standard. The HPLC-MS/MS was operated in the positive mode. Recovery ranged from 87.7 to 119% for tetracyclines, 83.3 to 110.3% for fluoroquinolones and 71.9 to 103.8% for aminoglycosides. The validated method was suitable for the intended use. 890 milk samples from PAMVet were evaluated. Overall, more than half (54.8%) of the samples contained some type of antibiotic. 18.4% of the samples contained doxycycline and norfloxacin residues, which are not allowed by Brazilian law in milk producing animals. Considering antibiotics use by geographic regions, the highest prevalence was observed in the southern region (66.4%), whereas in the northern region, the highest percentage of condemnation (27%) was observed.